Control y supervisión de un equipo de extrusión de plástico reciclado (2020)
In this article, it is specifically detailed the programming of the SIEMENS (PLC) s7 1200 1214c DC / DC / DC, as well as the human machine interface (HMI) KTP 700 to control the temperature of two heating resistors connected in parallel of an recycled plastic extrusion equipment. This requires of the reading of the analog signal of a temperature sensor RTD (resistance temperature detector) through one of the analog inputs of the PLC. The type of control used in closed loop feedback by integrating in this loop a PID controller which is included in the programming libraries of the PLC under the instruction PID_Compact, this instruction generates a PWM (Pulse Width Modulation) control signal that allows operating a solid state relay (SSR). In addition to this, they included, on the one hand, an independent routine that controls the operation of a three-phase motor together with its thermal protections that generates the directed movement and the torque necessary to perform the extrusion by means of a screw (endless screw) ) typical of conventional extrusion equipment. On the other hand, a routine was programmed that allows to modify the speed of a DC motor through a PWM signal, this motor generates the movement of the worm screw of the plastic material doser previously ground in flakes. For the supervision and control of the aforementioned conditions, an HMI was programmed, which has the option of controlling the temperature of the equipment manually or automatically.